Anti-nociceptive, anti-inflammatory and possible mechanism of antinociceptive action of methanol leaf extract of Nymphaea lotus Linn (Nymphaeceae) - Rege, Musa G.; Ayanwuyi, Lydia O.; Zezi, Abdulkadir U.; Odoma, Saidi (Journal of Traditional and Complementary Medicine, 2021)
The leaf of Nymphaea lotus has been used traditionally for the management of pain and inflammatory diseases. The methanol leaf extract of Nymphaea lotus (NLE) was evaluated for possible anti-nociceptive and anti-inflammatory activities in rats and mice (at the doses of 250, 500 and 1,000 mg/kg) to investigate the existence of scientific basis for the folkloric use of the plant. The standard drugs used were piroxicam (10 mg/kg) and morphine (10 mg/kg). The possible pharmacological mechanism involved in the anti-nociceptive activity was also investigated. The acute toxicity was determined in mice and rats using method of Lorke. The anti-nociceptive activity was evaluated using acetic acid-induced writhing and hot plate tests in mice, while the anti-inflammatory activity was evaluated using carrageenaninduced hind paw edema model in rats. The oral median lethal dose of NLE was found to be greater than 5,000 mg/kg in rats and mice. NLE demonstrated significant and dose-dependent protection against acetic acid induced writhes and increased the reaction time of mice in hot plate test. Pretreatment of the animals with naloxone (2 mg/kg) significantly (p < 0.05) attenuated the anti-nociception elicited by both NLE and morphine. NLE at the doses of 250 and 1,000 mg/kg significantly (p < 0.05) decreased rat paw edema at the 2nd hour in the carrageenan-induced paw edema test. The result of the study revealed that Nymphaea lotus possesses anti-nociceptive activities which may be mediated via the opioidergic system as well as mild anti-inflammatory activities thus providing scientific basis for the use of the plant in the management of pain and inflammatory diseases.
Keywords: Acetic acid; Analgesia; Anti-Inflammation; Nymphaea lotus; Hot plate test; Opioidergic